State of Formic Acid Dissolved in Tar According to Infrared Spectroscopy. Issue 1 (January 2023) - Paukshtis, Evgeniy A.; Chesnokov, Vladimir V.; Glazneva, Tatiana S.
Formic acid is considered as a promising hydrogen carrier and can be used as a source of hydrogen in the processing of heavy oil fractions such as tar. The interaction of formic acid with tar was studied by infrared Fourier transform spectroscopy via special technique using a mirror substrate. The infrared (IR) spectra were interpreted considering density functional theory (DFT) calculations. It was shown that formic acid dissolved in tar in three forms, as dimers, monomers of cis- and trans -configurations, hydrogen-bonded to the aromatic rings of the tar compounds, and as free-rotating gas molecules (microbubbles in the tar bulk). The research performed provides an opportunity and methodological base for studying the process of tar conversion in the presence of formic acid into gasoline fractions at temperatures up to 300 o C. Graphical Abstract